Medieval Qalhāt, historical vs archaeological data - Axelle Rougeulle (Arabian Humanities)
Qalhāt, in Oman, was one of the main hubs of the Indian Ocean trade at the time of the kingdom of Hormuz, in the 13th to 15th centuries AD. It is now an impressive archaeological site, a large ruined city about 35 ha wide. Excavations started there in 2008 with a French team under the authority of the Ministry of Heritage and Culture of Oman, and have since turned into an important development project with the final aim to create an archaeological park on site. Research have yielded considerable data about: the spatial organization and development of the town, its fortifications, the various quarters and main buildings including the Friday mosque, the daily life of its inhabitants and the trading activities of the port. Paralleled with literary sources they now give a clearer idea of the history of this main harbour of the medieval period.